PROTOCOL: Gender transformative approaches in agriculture for women's empowerment: A systematic review. Issue 3 (9th July 2022) - Singh, Sabina; Mohan, Ashima; Saran, Ashrita; Puskur, Ranjitha; Mishra, Avni; Etale, Linda; Cole, Steven Michael; Masset, Edoardo; Waddington, Hugh Sharma; MacDonald, Heather; White, Howard
Abstract: This is the protocol for a Campbell systematic review. The objective of this systematic review is to assess the effectiveness of interventions with gender transformative approach (GTA) components in improving women's empowerment in low‐ and middle‐income countries, and to curate evidence on the mechanisms through which GTA works to improve women's empowerment in agriculture.